Prevalence of COVID-19 in health professionals and occupational psychosocial risks - Sousa-Uva, Mafalda (2021)
Introduction: Health professionals who provide clinical care are exposed to patients potentially infected by the severe acute respiratory syndrome coronavirus 2 SARS-CoV-2), namely physicians and nurses; consequently, these professionals face higher risks of infection. Objectives: This study aimed to describe the prevalence of coronavirus disease 19 (COVID-19) cases among health professionals and the frequencies of risk factors and psychosocial risk. Methods: This is a cross-sectional study targeted at health professionals working in Portugal during the current COVID-19 pandemic. Data were obtained through a self-administered questionnaire available online at the websites of medical and nursing boards, among other sources. We performed a univariate analysis, calculating absolute and relative frequencies, and a bivariate analysis with a Pearson's chi-squared test. Results: We studied 4,212 health professionals, of which 36.7% (n = 1,514) worked in areas dedicated to the treatment of sick or suspected COVID-19 patients. Of these, 2.11% tested positive for SARS-CoV-2. Among all participants, 76.7% and 79.1% presented moderate to severe levels of fatigue and anxiety, respectively. Fatigue levels were significantly higher in professionals working in areas dedicated to the treatment of patients with COVID-19 (80.5% p = 0.01), but this difference was not observed regarding anxiety (79.5% p = 0.681). Conclusions: The percentage of health professionals who tested positive for SARS-CoV-2 was 2.11%. The reported high levels of fatigue and anxiety should determine a better protection of the health and safety of those who provide health care in the current pandemic.